2012
DOI: 10.1124/jpet.111.189225
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Modifies Overflow and Presynaptic Compartmentalization of Dopamine via an α-Synuclein-Dependent Mechanism

Abstract: Methylphenidate (MPD) modulates dopamine (DA) overflow in part by redistributing vesicle pools, a function shared by the presynaptic protein ␣-synuclein (␣-syn). We suggest that ␣-syn modifies the effect of MPD on DA neurotransmission. The effect was studied in the dorsal striatum in wild-type mice and two mouse lines lacking ␣-syn by using in vivo voltammetry and microdialysis. MPD (1 mg/kg) attenuated evoked DA overflow only in mice lacking ␣-syn but produced a similar increase in the extracellular DA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…6E). This evidence seems in line with previous findings that showed that repeated-burst stimulation, which redistributes vesicular storage pools and facilitates dopamine overflow, is enhanced in C57BL/6JOlaHsd mice (Chadchankar et al, 2012). The increased responsiveness of these mice to cocaine or repeated-burst stimulation might be explained by the selective increase of synapsin III in the striatum.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…6E). This evidence seems in line with previous findings that showed that repeated-burst stimulation, which redistributes vesicular storage pools and facilitates dopamine overflow, is enhanced in C57BL/6JOlaHsd mice (Chadchankar et al, 2012). The increased responsiveness of these mice to cocaine or repeated-burst stimulation might be explained by the selective increase of synapsin III in the striatum.…”
Section: Resultssupporting
confidence: 81%
“…Cocaine abuse elevates α-syn levels in the human striatum (Qin et al, 2005), whereas overexpression of α-syn in the nucleus accumbens influences the behavior of rats in response to cocaine (Boyer and Dreyer, 2007). Furthermore, methylphenidate, which like cocaine is able to affect exocytotic dopamine release from synaptic vesicles (Volz et al, 2008), modifies overflow and presynaptic compartmentalization of dopamine through an α-syn-dependent mechanism (Chadchankar et al, 2012). All of these results suggest that drugs which mobilize dopamine vesicle pools act by regulating the function of α-syn-synapsin-III complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the first study to show enhanced MPH-induced dopamine release following MPH self-administration, it is possible that dopamine transporter levels influence these effects as well. MPH has been shown to redistribute vesicles from storage pools into the readily releasable pool (Chadchankar et al, 2012; Volz et al, 2008). This could be a potential mechanism for its release effects and it is possible that these effects could be dependent on MPH binding to the dopamine transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cocaine has been found to up-regulate vesicular dopamine release in several preparations, including brain-slice [ 53,54 ], anesthetized [ 55-57 ], and awake [ 58 ]. Up-regulation of dopamine release has more recently been extended to methylphenidate, a cocaine-like DAT-I [ 59 ], and surprisingly, even AMPH [ 42,55,56,60 ]. It should be emphasized that the evidence for up-regulated dopamine release by addictive DAT-Is is typically based on studies using a single dose administered non-contingently.…”
Section: Actions Of Abused Drugs On Dopamine Neurons: New Viewmentioning
confidence: 99%